2020
DOI: 10.1002/pep2.24156
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of receptor binding to collagen by glycosylated 5‐hydroxylysine: Chemical biology approaches made feasible by Carpino's Fmoc group

Abstract: The creation of the 9‐fluorenylmethoxycarbonyl (Fmoc) group by the Carpino laboratory facilitated the synthesis of peptides containing acid‐sensitive groups, such as O‐linked glycosides. To fully investigative collagen biochemistry, one needs to assemble peptides that possess glycosylated 5‐hydroxylysine (Hyl). A convenient method for the synthesis of Fmoc‐Hyl(ε‐tert‐butyloxycarbonyl (Boc), O‐tert‐butyldimethylsilyl [TBDMS]) and efficient methods for the synthesis of Fmoc‐Hyl[ε‐Boc,O‐(2,3,4,6‐tetra‐O‐acetyl‐β‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…195 Direct incorporation of hydroxylysine is a step to producing synthetic collagen without the need for animal sources. 196 Zhang et al have produced a polypeptide scaffold for protein immobilization using p-azidophenylalanine (pAzF), an ncAA that generates covalent linkages to substrates upon UV irradiation. 197 By using a mutant E. coli phenylalanyl-tRNA synthetase (A294G), they partially replace the phenylalanine residues in their polypeptide with pAzF, producing a material that can effectively immobilize recombinant proteins.…”
Section: Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation
“…195 Direct incorporation of hydroxylysine is a step to producing synthetic collagen without the need for animal sources. 196 Zhang et al have produced a polypeptide scaffold for protein immobilization using p-azidophenylalanine (pAzF), an ncAA that generates covalent linkages to substrates upon UV irradiation. 197 By using a mutant E. coli phenylalanyl-tRNA synthetase (A294G), they partially replace the phenylalanine residues in their polypeptide with pAzF, producing a material that can effectively immobilize recombinant proteins.…”
Section: Cross-linkingmentioning
confidence: 99%
“…These aldehydes then condense with one another to form pyridinoline cross-links. , It has been demonstrated that supplementing tissue-engineered neocartilage with hydroxylysine and copper sulfate significantly increases its pyridinoline cross-links, resulting in a 3.3-fold increase in the tensile strength of the material . Direct incorporation of hydroxylysine is a step to producing synthetic collagen without the need for animal sources …”
Section: Applications Of Residue-specific Noncanonical Amino Acid Inc...mentioning
confidence: 99%